5,6-Dihydro-(1,2,4)triazolo(1,5-с)quinazolines. Message 1. Features of interactions between (2-(3-aryl-1H-1,2,4-triazole-5-yl)phenyl)amines, aliphatic and aromatic aldehydes - Kholodnyak, S. V.; Schabelnyk, K. P.; Voskoboynik, O. Yu.; Berest, G. G.; Kovalenko, S. I.; Холодняк, Сергій Валерійович; Шабельник, Костянтин Петрович; Воскобойнік, Олексій Юрійович; Берест, Галина Григорівна; Коваленко, Сергій Іванович (Харків: НФаУ, 2015)
Reactions of [5+1]-cyclocondensation of [2-(3-aryl-1H-1,2,4-triazol-5-yl)phenyl]amines with aliphatic and aromatic aldehydes produce the corresponding 5-R-2-aryl-5,6-dihydro- or 5-R-2-aryl-[1,2,4]triazolo[1,5-с]quinazolines depending on the conditions. The optimal conditions of the reaction have been found, and factors contributing to oxidation of 5-R-2-aryl-5,6-dihydro-[1,2,4]triazolo[1,5-с]quinazolines have been determined. The alternative synthetic approaches for 5-R-2-aryl-[1,2,4]triazolo[1,5-с]quinazolines, namely oxidation of their reduced analogues and interaction of [2-(3-aryl-1H-1,2,4-triazol-5-yl)phenyl]amines with acylhalides of aliphatic or aromatic carboxylic acid have been proposed. Purity and the structure of the compounds synthesized have been confirmed by the complex of physicochemical methods, including LC-MS, 1H-, 13C NMR, mass-spectrometry and elemental analysis. The peculiarities and differences of 1H- and 13C-NMR spectral patterns of 5-R-2-aryl-5,6-dihydro-[1,2,4]triazolo[1,5-с]quinazolines and their aromatic analogues have been described. Реакції [5+1]-циклоконденсації [2-(3-арил-1H-1,2,4-триазол-5-іл)феніл]амінів з альдегідами аліфатичного та ароматичного ряду в залежності від умов проведення перебігають з утворенням 5-R-2-арил-5,6-дигідро- або 5-R-2-арил-[1,2,4]триазоло[1,5-с]хіназолінів. Визначені оптимальні умови реакції та встановлені основні фактори, які сприяють окисненню 5-R-2-арил-5,6-дигідро-[1,2,4]триазоло[1,5-с]хіназолінів. Розроблені методи зустрічного синтезу 5-R-2-арил-[1,2,4]триазоло[1,5-с]хіназолінів: окисненням їх гідрованих аналогів або взаємодією [2-(3-арил-1H-1,2,4-триазол-5-іл)феніл]амінів з хлорангідридами відповідних алкіл(арил)карбонових кислот. Індивідуальність та будова синтезованих сполук підтверджена хроматомас-, 1Н-, 13С-ЯМР-спектрами та елементним аналізом. Показані особливості та відмінності резонування характеристичних протонів 5-R-2-арил-5,6-дигідро-[1,2,4]триазоло[1,5-с]хі-назолінів та їх ароматичних аналогів.
5,6-Дигідро-[1,2,4]триазоло[1,5-с]хіназоліни. Повідомлення 1. Особливості поведінки [2-(3-арил-1H-1,2,4-триазол-5-іл)феніл]амінів в реакціях з альдегідами аліфатичного та ароматичного ряду
Keywords: 5-[2-(3-aryl-1H-1,2,4-triazol-5-yl)phenyl]amines; [5+1]cyclocondensation; spectral characteristics; [2-(3-арил-1H-1,2,4-триазол-5-іл)феніл]аміни; [5+1]-циклоконденсація; спектральні характеристики